Pengaruh Kualitas Layanan dan Persepsi Harga terhadap Kepuasan Pelanggan di PT. Sucofindo (Persero) Cabang Surabaya - Aghita Reza Meita Putri; Supriyono Supriyono (J-MAS (Jurnal Manajemen dan Sains), 2022)
Customer satisfaction will be formed if it can meet the basic expectations of customers. Many factors affect customer satisfaction, including service quality and price perception. The problems in this research are (1) whether service quality has an effect on customer satisfaction of PT. Sucofindo Surabaya ?, (2) does price perception affect customer satisfaction of PT. Sucofindo Surabaya ? The purpose of this study was to determine the effect of service quality and price perception on customer satisfaction at PT. Sucofindo Surabaya . The total population of this study are customers of PT. Sucofindo Surabaya . The sample that uses 60 respondents is taken by the Non-Probability Sampling technique with the Accidental Sampling approach. This study uses quantitative methods using structural equation modeling and data processing using the Partial Least Square (PLS) method. The results showed that the service quality variable (X1) and price perception (X2) had a significant and positive effect on customer satisfaction (Y).